ANALISIS KINERJA TEKNOLOGI JARINGAN WIRELESS PADA FREKUENSI 2.4 GHz DALAM KONDISI RUANGAN TERTENTU - Muhammad Arif Setyawan; Suwanto Raharjo; Erna Kumalasari N (Jurnal Jarkom, 2016)
Transmission media needed to perform the test measurement data and to determine the performance of an existing wireless network in two different rooms. One of the transmission medium that can be used is the access point that has been connected to the server computer. The access point is required to emit a wifi signal so that the client computer can access to the server computer. Testing wireless network performance could be the solution to determine the performance of wireless networks.Implementation of wireless network performance testing used a server computer, the client computer and an access point. Testing is done by analyzing the parameters of Quality of Service (QOS) including delay, packet loss, jitter, throughput, signal strength, upload and download speeds. The tests are carried out in two different rooms and each room is done testing on two different access point placement. The method used was study of literature, network design and implementation of wireless network testing.On test results performance of a wireless network in a room divider wall first obtained on the current average, the signal strength is weak, and the barrier wall 2 obtained test results on good average, with the signal strength is good, the barrier triplex 1 obtained test results nice average and signal strength, as well as on limiting triplex 2 obtained very good results and also good signal strength. Overall wireless networks in two different rooms is able to perform well, but the barrier at about access point makes wireless network signal is disrupted and it can affect the performance of wireless networks.